Alleviating Salinity Stress in Almond Plants through Rhizophagus irregularis Inoculation: A Greenhouse Study - Otabek Bobojonov; Uday Abdul-Reda Hussein; Ali Obaid Hajray; Mohaned Mohammed Hani; Salam Ahjel; Amran Mezher Lawas; Abed J. Kadhim; Sada Ghalib Al- Musawi; Manzura Kamalova; H.F. Hamroev; Jurabekova Khabiba; A.K. Mukhiddin Ugli (Journal of Nuts, 2024)
Soil salinity significantly limits crop productivity. This study explores the role of the mycorrhizal fungus Rhizophagus irregularis (Ri) in enhancing the antioxidant system and pigment concentrations in almond plants (Prunus dulcis) under salinity stress, aiming to reduce salt-induced toxicity and offer potential solutions for saline agriculture. The experiment used almond seeds grown under varying salinity levels (0, 25, 50, and 100 mM NaCl) and Ri inoculation. Parameters including root colonization percentage, growth parameters, plant pigment concentrations, and antioxidant enzyme activity were analyzed. Results revealed that salinity significantly impacted all parameters, with a notable reduction in both wet and dry weights of shoots and roots as salinity increased. Shoot dry weight decreased from 1.87 g to 0.58 g in Ri plants and from 1.39 g to 0.60 g in non-Ri plants as salinity increased from 0 to 100 mM NaCl. Additionally, root colonization by Ri showed a significant decrease from 47.12% under non-saline conditions to 8.23% under high salinity (100 mM NaCl). Ri treatment had a significant effect on several parameters except for carotenoid levels and catalase enzyme activity. For instance, Ri inoculation resulted in increased chlorophyll levels (from 3.57 mg g-1 to 4.78 mg g-1 in control plants and from 1.58 mg g-1 to 2.21 mg g-1 under high salinity) and flavonoid quantities (from 4.78 mg g-1 to 5.80 mg g-1 in control plants and from 6.46 mg g-1 to 6.68 mg g-1 under high salinity) compared to non-inoculated plants, irrespective of salinity conditions. The data also demonstrated that salinity was the primary determinant of catalase enzyme activity in both shoot and root tissues, with a corresponding increase in catalase activity as salinity increased. For instance, shoot catalase activity increased from 1.30 mg protein min-1 to 2.35 mg protein min-1 in Ri plants and from 1.16 mg protein min-1 to 2.24 mg protein min-1 in non-Ri plants with increasing salinity. In conclusion, Ri inoculation can potentially mitigate the adverse effects of salinity in almond plants by enhancing certain growth parameters and antioxidant activity, as indicated by the statistically significant interactions between salinity and Ri.